Pelatihan Dasar-Dasar Manajemen Proyek Menggunakan Perangkat Lunak Primavera P6 Bagi Alumni dan Mahasiswa Tingkat Akhir Lintas Universitas - Dimaz Harits; Kuswandi Arifin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Project management is the management of human and material resources to achieve targets that include quality, scheduling, cost, and stakeholder expectations. Industry 4.0 affects business processes, including in the construction field. The Primavera P6 Professional Project Management Fundamentals training, which is part of the Ministry of Communication and Information Technology's 2022 Digital Talent Scholarship program, aims to improve the productivity of young construction industry talent by enhancing their understanding of technology and automation. The training uses synchronous Zoom-based methods and lasts for four weeks plus one final exam day. Out of a total of 26 participants, five people successfully achieved the passing grade score and followed the international competency test certification for Oracle Primavera P6, which was held by Oracle University.